PENGARUH KEPEMIMPINAN ALTRUISTIC TERHADAP PERILAKU MENOLONG, DIMEDIASI OLEH WORK ENGAGEMENT DAN EMOSI POSITIF - Arifin S, Rony Tondy; Abdillah, Muhammad Rasyid; Indarti, Indarti (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the effect of altruistic leadership on helping behavior among village officials, using work engagement and positive emotions as mediating variables. This study used a quantitative approach with data collection through closed-ended questionnaires distributed to 156 village officials in several villages within the administrative area of Sialang Pasung Village. The research instrument was developed based on indicators from theory and previous studies. Data analysis used the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method to test the direct and indirect relationships between variables. The results showed that altruistic leadership significantly influenced helping behavior, both directly and through the mediation of work engagement and positive emotions. Work engagement was found to be the strongest mediator in strengthening this relationship. These findings confirm that a leadership style that emphasizes caring and sincerity contributes significantly to building work morale and encouraging prosocial behavior within village officials. Therefore, strengthening altruistic values in leadership practices is a strategic step in realizing more humanistic, productive, and collaborative village governance. Keywords: altruistic leadership, helping behavior, work engagement, positive emotions, SEM-PLS